Penicillium Purpurogenum Produces a Novel, Acidic, gh3 Beta-Xylosidase: Heterologous Expression and Characterization of the Enzyme - (:unkn) unknown (ELSEVIER SCI LTD, 2019)
Xylan, a component of plant cell walls, is composed of a backbone of beta-1,4-linked xylopyranosyl units with a number of substituents. The complete degradation of xylan requires the action of several enzymes, among them beta-xylosidase. The fungus Penicillium purpurogenum secretes a number of enzymes participating in the degradation of xylan. In this study, a beta-xylosidase from this fungus was expressed in Pichia pastoris, and characterized. This enzyme (Xyl2) is a member of glycoside hydrolase family 3; it consists of a sequence of 792 residues including a signal peptide of 20 residues, with a theoretical molecular mass for the mature protein of 84.2 KDa and an isoelectric point of 5.07. The highest identity with a characterized fungal enzyme, is with a beta-xylosidase from Aspergillus oryzae (70%). The optimal activity of Xyl2 is found at pH 2.0 and 28 degrees C. The enzyme is most stable at pH 2.0 and conserves 40% of activity at 42 degrees C (after 1h incubation). The kinetic parameters for p-nitrophenyl-beta-D-xylopyranoside are: K-M 0.53 mM, kcat 1*10(7) s(-1) and kcat/K-M 1.9*10(10) M-1 s(-1). The enzyme is about 10% active on p-nitrophenyl-alpha-L-arabinofuranoside. Xyl2 exhibits a high hydrolytic activity on xylooligosaccharides; it liberates xylose from beechwood and birchwood glucuronoxylan and it acts synergistically with endoxylanases in the degradation of xylan. Its low pH optimum make this enzyme particularly useful in potential applications requiring a low pH such as increasing the flavor of wine.